2022
DOI: 10.2478/jtim-2021-0051
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of autophagy in triptolide-induced apoptosis of TM3 Leydig cells

Abstract: Background and Objectives Triptolide (TP) is known to impair testicular development and spermatogenesis in mammals, but the mechanism of the side effects still needs to be investigated. The aim of the research is to confirm whether TP can cause autophagy in TM3 Leydig cells and the potential molecular pathway in vitro. Methods TM3 Leydig cells are used to investigate the molecular pathway through Western blot, detection of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Our experimental results also confirmed that the changes in the levels of these two proteins during the inhibition of tumor development by niclosamide were consistent with previous studies. There is also some evidence for the ability of niclosamide to suppress colon cancer cell growth via inducing the formation of autophagosomes 38 , 39 . As such, this drug may engage a range of context-specific mechanisms to exert its antitumor effects, emphasizing the need for further research focused on these topics.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental results also confirmed that the changes in the levels of these two proteins during the inhibition of tumor development by niclosamide were consistent with previous studies. There is also some evidence for the ability of niclosamide to suppress colon cancer cell growth via inducing the formation of autophagosomes 38 , 39 . As such, this drug may engage a range of context-specific mechanisms to exert its antitumor effects, emphasizing the need for further research focused on these topics.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has illuminated autophagy's multifaceted regulation, involving an intricate interplay between inflammation and apoptosis. [22][23][24] In macrophages, autophagy induction has been proposed to exert an anti-inflammatory effect, while inhibition of autophagy has been linked to enhanced apoptosis. 25,26 Many studies have indicated that autophagy takes part in the recovery of kidney during AKI.…”
Section: Introductionmentioning
confidence: 99%